NEUROVEGETATIVE VIOLATIONS IN THE PATHOGENESIS OF VITILIGO - R.A. RAKHIMOV; K.M. MUKHAMADIEVA; S.S. ISMATULLOEVA (Паёми Сино, 2017)
This article presents an analysis of contemporary publications dedicated to actuals of the role of neurovegetative disorders in the pathogenesis of vitiligo. Based on the generalized literary data, the authors focus on the relationship of vitiligo with disorders of various parts of the nervous system, leading to damage and degeneration of melanocytes. The chronic, progressive course of vitiligo, caused by the activity of the immune system and stimulated by neurovegetative dysbiosis, is directly related to the psychological reaction of the person for the presence of a cosmetic defect.This article presents an analysis of contemporary publications dedicated to actuals of the role of neurovegetative disorders in the pathogenesis of vitiligo. Based on the generalized literary data, the authors focus on the relationship of vitiligo with disorders of various parts of the nervous system, leading to damage and degeneration of melanocytes. The chronic, progressive course of vitiligo, caused by the activity of the immune system and stimulated by neurovegetative dysbiosis, is directly related to the psychological reaction of the person for the presence of a cosmetic defect.